2014
DOI: 10.1007/s00345-014-1401-7
|View full text |Cite
|
Sign up to set email alerts
|

Sacral neuromodulation and Botulinum toxin A for refractory idiopathic overactive bladder: a cost-utility analysis in the perspective of Italian Healthcare System

Abstract: A therapeutic strategy starting with SNM may be considered cost effective in the midterm and cost saving in the long-term treatment of idiopathic OAB from the INHS perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…The rechargeable Axonics r‐SNM System is designed to have a 15‐year life. This rechargeable SNM system may further enhance the cost‐superiority of SNM compared to Botox and percutaneous tibial nerve stimulation . The long‐term follow‐up of this study will provide data to assess the cost implications of the system and validate the longevity of the device as well as provide insights into patient preference for a rechargeable system.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The rechargeable Axonics r‐SNM System is designed to have a 15‐year life. This rechargeable SNM system may further enhance the cost‐superiority of SNM compared to Botox and percutaneous tibial nerve stimulation . The long‐term follow‐up of this study will provide data to assess the cost implications of the system and validate the longevity of the device as well as provide insights into patient preference for a rechargeable system.…”
Section: Discussionmentioning
confidence: 93%
“…The rechargeable SNM device, modeled with a 10‐year life, was projected to save the United States healthcare system $12 billion over a 15‐year period . Non‐rechargeable SNM therapy has been shown to be a cost‐effective long‐term treatment of OAB in Europe and Canada, including studies showing that SNM is more cost‐effective than other third line OAB therapies . The rechargeable Axonics r‐SNM System is designed to have a 15‐year life.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in the Canadian, Italian, and the UK healthcare systems, SNM was estimated to be more cost‐effective in the long term . Furthermore, the use of different models based on a great variance of clinical parameters could also contribute to the conflicting results of comparative cost‐effectiveness studies. A stark example is a study based on the Dutch healthcare system whereupon SNM was found to be more cost‐effective than Botox® after 4 years of treatment but with a model using general anesthesia for both procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Bertapelle et al found that higher initial costs of SN were balanced out by excellent long-term outcomes. It was found to be cost-effective after 3 years and more cost-effective, with both lower cost and higher efficacy, than botulinum toxin A at 10 years 33. In Spain, the authors used incremental cost-effectiveness ratios to determine the incremental cost per quality-adjusted life year gained.…”
Section: Cost-effectivenessmentioning
confidence: 99%